Optimization of Process Variables in Esterification of iso-Octanol with Acetic Acid using Acid Ionic Liquid as Catalyst - Huan, Du; Lelian, Song; Zhongqin, Tan; Han*, Xiaoxiang (Asian Journal of Chemistry, 2014)
Response surface methodology was successfully applied to optimize esterification of iso-octanol with acetic acid. The effects of various reaction conditions, including reaction time, substrate molar ratio, the amount of catalyst and the amount of water carrying agent were investigated. A Box-Behnken Design was employed to search for the optimal yield of iso-octyl acetate. The analysis confirmed that the reaction time and the amount of water carrying agent were the significant factors affecting the yield of iso-octyl acetate. The coefficient of determination of the model was 0.8922. Under the optimized conditions, the yield of iso-octyl acetate reached 95.35 %, in close agreement with values predicted by the mathematical model. The ionic liquids could be reused five times without noticeable drop in activity.